Case report: Relapse of intrathyroidal parathyroid carcinoma in a patient with novel variants in MET and CDKN1C genes - Kim, Ekaterina; Lavreniuk, Anastasiia; Spasskaya, Olga; Eremkina, Anna; Salimkhanov, Rustam; Urusova, Liliya; Tarbaeva, Natalia; Popov, Sergey; Zakharova, Victoria; Mokrysheva, Natalia (Frontiers in Oncology, 2025)
Parathyroid carcinoma (PC) is one of the rarest malignant neoplasms of the human endocrine system, with a prevalence of approximately 0.005% of all oncological diseases. Despite its indolent course, PC generally relapses in about 40%–60% of cases. The severity of the disease is usually determined by uncontrolled life-threatening hypercalcemia. Currently, there are no reliable criteria for preoperative diagnosis of PC; moreover, topical diagnosis and morphologic examination remain challenges. Surgery remains the gold standard for the treatment of both primary tumors and distant metastases. Other treatment options, such as chemotherapy or immunotherapy, are limited. Targeted therapy is considered a promising direction for disseminated tumors. We present a clinical case of a 70-year-old female patient with recurrent intrathyroidal PC and distant lung metastases, with novel variants in the MET and CDKN1C genes.